The Role of the Nurse Regulator in the Mobile Emergency Care Service: A Literature Review - , Gleyce Pinto Girard; , Adriete Malato Ferreira Cordovil dos Santos; , Joubert Fontenelle Souza Leite; , Thamyris Abreu Marinho Rodrigues; , Simone do Socorro de Souza Ribeiro; , Allan Kardec Lima Brandão; , Andressa Torres Oliveira; , Sandy Costa dos Santos; , Andreza Sena Machado; , Lis Ferreira Barbosa; , Kélia das Graças de Paiva Macias Nakai; , Mayk Kevin Lobo Moraes; et al. (Archives of Current Research International, 2025)
This study aims to evaluate the scientific literature on the role of nurse regulators in the mobile emergency care service (SAMU). This is a qualitative study of the narrative literature review type, carried out through a search in the BVS, PubMED, and Google Scholar databases, which selected texts published between 2019 and 2024. The results show that nurse regulators perform functions in SAMU such as receiving and evaluating emergency calls, performing triage and risk classification of cases, in order to direct care appropriately; providing pre-hospital guidance to callers; recording and documenting all care information, contributing to the continuity of care and the assessment of the quality of the service provided, in addition to the need for effective communication and decision-making skills. These skills include technical knowledge and resource management. They must have a solid knowledge of SAMU protocols and guidelines, given that they need to quickly analyze the available information and direct the team accurately and efficiently. It is concluded that the nurse regulator is essential in the SAMU triage and regulation system, ensuring that medical care is directed efficiently and effectively. The complexity of their functions reflects the importance of robust and continuous training, aimed at improving technical skills and rapid decision-making. However, they face significant challenges such as work overload, which requires resilience and adequate organizational support to sustain the quality of care amid high demand.